In all cases, if
has real coefficients, then any complex roots occur in conjugate pairs, so if
is a root, then so is
. Also, by the fundamental theorem of algebra, if
are roots to
, then for some constant
,
![f(x)=a(x-r_1)\cdots(x-r_n)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gbg7qkio03mngwxunxpcwbomr8dx4revrj.png)
1. If
and
, then
![f(x)=a(x-3)(x-2i)(x+2i)=ax^3-3ax^2+4ax-12a](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lfqks12no3ebau4rpxexlixpyal3vhlmjz.png)
Given that
, we have
![f(-1)=a(-1-3)(-1-2i)(-1+2i)=-20a=50\implies a=-\frac52](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cqdq3k499e3yvnx970nb2moffyslgzc6gg.png)
![\implies\boxed{f(x)=-\frac52x^3+\frac{15}2x^2-10x+30}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qhr46edtzr51pv5rsj90rc4x502bg9h3eh.png)
2.
![f(x)=a(x-4)(x-(-5+2i))(x-(-5-2i))=a x^3 + 6 a x^2 - 11 a x - 116 a](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3w6ku2ag05xcrnrp7gc2g3y27f0hjidsv9.png)
With
, we have
![f(2)=a(2-4)(2+5-2i)(2+5+2i)=-106a=-636\implies a=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kt5w3avm34lp0mmvxqgwh1ahre0x2whs1x.png)
![\implies\boxed{f(x)=6x^3+36x^2-66x-696}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/amd3bl9u6i9bvllrjseyp10h45v8gj4167.png)
The rest are done in the same exact way.